A Ruskin Chronology - Bradley, J. author. aut Link
XII, 129 p.
Keywords: The theme and scope of the Chronology focus on the life (in bare outline) and publications (in temporal order) of John Ruskin (1819-1900). As art-critic, social commentator, architectural scholar, geologist, botanist, water-colourist, lecturer, letter-writer and prose stylist, Ruskin stands forth as perhaps the pre-eminent Victorian polymath. His advocacy of art and artists, his courage in the face of hostile, uninformed criticism and his enlightened compassionate views of the human condition reveal Ruskin as 'not of an age but for all time'. These attributes the Chronology endeavours to suggest.